Sphingosine-1-Phosphate/Sphingosine-1-Phosphate Receptor 2 Axis Can Promote Mouse and Human Primary Mast Cell Angiogenic Potential through Upregulation of Vascular Endothelial Growth Factor-A and Matrix Metalloproteinase-2 - Alena Chumanevich; Piper Wedman; Carole A. Oskeritzian (Mediators of Inflammation)
Mast cells (MC) are present in most vascularized tissues around the vasculature likely exerting immunomodulatory functions. Endowed with diverse mediators, resident MC represent first-line fine-tuners of local microenvironment. Sphingosine-1-phosphate (S1P) functions as a pluripotent signaling sphingolipid metabolite in health and disease. S1P formation occurs at low levels in resting MC and is upregulated upon activation. Its export can result in type 2 S1P receptor- (S1PR2-) mediated stimulation of MC, further fueling inflammation. However, the role of S1PR2 ligation in proangiogenic vascular endothelial growth factor- (VEGF-) A and matrix metalloproteinase- (MMP-) 2 release from MC is unknown. Using a preclinical MC-dependent model of acute allergic responses and in vitro stimulated primary mouse bone marrow-derived MC (BMMC) or human primary skin MC, we report that S1P signaling resulted in substantial amount of VEGF-A release. Similar experiments using S1pr2-deficient mice or BMMC or selective S1P receptor agonists or antagonists demonstrated that S1P/S1PR2 ligation on MC is important for VEGF-A secretion. Further, we show that S1P stimulation triggered transcriptional upregulation of VEGF-A and MMP-2 mRNA in human but not in mouse MC. S1P exposure also triggered MMP-2 secretion from human MC. These studies identify a novel proangiogenic axis encompassing MC/S1P/S1PR2 likely relevant to inflammation.